Analisis Faktor Risiko Gout Arthritis - Irmawati RJ; Elsi Tandi Pailan; Baharuddin Baharuddin (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Gout arthritis is an inflammatory disease in the joints, which is still very high and is still a public health problem, especially in Indonesia with a high prevalence. This study aims to determine the risk factors that influence the incidence of Gout arthritis. Quantitative research with a case control study approach. A sample of 60 respondents was 30 each for the case and control groups. The instrument used in this study was in the form of a questionnaire or questionnaire. The data were analyzed using the chi-square test. Genetic statistical test results with values p = 0.002 (<0.05) OR = 6.909 (95% Cl 2.160-22.098), while uric acid levels and purine consumption with p values = 0.558 (>0.05), OR = 1.556 (95% Cl 0.534-4.532) and p = 0.055 (>0.05), OR = 3,500 (95% Cl 1,112-11,017). The conclusion that genetics have a significant influence, while uric acid levels and foods containing purines have no influence on Gout arthritis